Predictors of Arab American adolescent tobacco use - Kulwicki, Anahid (2006)
This study examined personal, psychosocial, sociocultural, and environmental predictors in tobacco use for 1671 Arab American adolescents. Cigarette smoking in past 30 days was 6.9%. This increased from 1% at age 14 to 14% at age 18. Twenty-nine percent of the youths reported ‘ever cigarette smoking.’ Experimentation with narghile was 27%; it increased from 23% at 14 years to 40% at 18 years. All trends were significant (p < .001). Logistic regression analyses found ten predictors for ‘smoked a cigarette in past 30 days’ and nine and seven, respectively, for ‘ever smoked a cigarette or narghile’. Friends and family members smoking were the strongest predictors of cigarette smoking and ‘ever narghile use.’ ‘Ever narghile use’ supported cigarette smoking.